Strategy Personalization Content on Vidio Application To Increase User Loyalty Through Satisfaction, Trust And Commitment - Ghazsani, Annizsa (Fakultas Ekonomi Universitas Gresik, 2023)
In the competitive landscape of video streaming platforms, Vidio company recognizes the importance of implementing effective strategies to enhance users loyalty. The study utilizes both primary and secondary data to analyze the impact of personalization content, satisfaction, trust and commitment on users loyalty. The primary data for this study were collected through the distribution of questionnaires to consumers who use the Vidio application platform. Additionally, secondary data from a literature review were used to analyze internal and external factors. The findings of this study support the corresponding hypothesis by showing that pleasure and trust have a favorable or substantial impact on users' loyalty to the Vidio application platform. However, according to PLS analysis, personalisation, commitment, and content seem to have little or a positive but insignificant impact on users' loyalty. In contrast, factor analysis and linear regression analysis, on the other hand, show a considerable impact. These results provide valuable insights for Vidio and similar platforms to focus on enhancing users satisfaction and building trust as key drivers of users loyalty. Further research is recommended to explore alternative strategies to improve personalization content and commitment in the Vidio application platform, as well as investigating additional factors that may influence users loyalty. By addressing these aspects, video streaming platforms can better understand and cater to users’ needs, ultimately fostering stronger users loyalty and long-term engagement.